Investigating Fear of Missing Out in Underpinning Nomophobia: A Perspective of College Students - Naz, Iram; Masood, Zarafshan; Akram, Neelam (Regional Lens, 2025)
As smartphone usage by college students grows, a number of psychological issues, such as nomophobia (the fear of being without one's phone) arise from heavy reliance on smartphones. Beyond this, increasing use of smartphones and increasing digital interaction is also linked to FoMo (or fear of missing out). The objective of this research study was to examine whether or fear of missing out influences the nomophobia in College students. A cross-sectional correlational design was used to collect data on students enrolled in government intermediate and undergraduate programs with the use of a convenient sampling method and with completion of three data collection instruments: the Nomophobia Questionnaire (Urdu), FoMo Scale, and Demographic Information. Simple Regression Analysis was performed using SPSS 24, and the results indicated that or fear of missing out was a significant predictor of nomophobia (F (1, 498) = 56.99, p <.001). Thus, not only does an individual with higher levels of or fear of missing out have greater nomophobia than does an individual who experiences lower or fear of missing out but also 10.3% of the variance in nomophobia (R2=.103) as predicted by the or fear of missing out regression model and a beta coefficient of (β=0.320). These results corroborate prior studies indicating that an individual with higher levels of or fear of missing out tends to overindulge in excessive use of smartphones and, when not engaging in smartphone activity, experiences heightened levels of anxiety.